GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 12028 species occurrences available in GBIF matching the query: TaxonKey: Aquila rapax (Temminck, 1828) HasCoordinate: true. The dataset includes 12028 records from 27 constituent datasets: 60 records from National Biodiversity Data Bank. Observation records, 1900-2014. 28 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 3635 records from Southern African Bird Atlas Project. 1 records from DMNS Bird Collection (Arctos). 3892 records from EOD - eBird Observation Dataset. 25 records from iNaturalist Research-grade Observations. 111 records from naturgucker. 1 records from SBMNH Vertebrate Zoology. 9 records from LACM Vertebrate Collection. 9 records from Natural History Museum (London) Collection Specimens. 6 records from Macaulay Library Audio and Video Collection. 1 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 6 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 1 records from Biologiezentrum Linz. 188 records from Israel Nature and Parks Authority. 4 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 40 records from Naturalis Biodiversity Center (NL) - Aves. 3338 records from Southern African Bird Atlas Project 2: Full protocol records. 135 records from BioGIS - Birds - INPA database. 1 records from MVZ Egg and Nest Collection (Arctos). 461 records from SAFRING: Historical Bird Ringing Records (2005-2009). 17 records from rmca-albertine-rift-birds. 1 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 39 records from UMMZ Birds Collection. 1 records from IICT Colecção Zoológica. 1 records from MVZ Bird Collection (Arctos). 17 records from Royal Museum of Central Africa - Albertian Rift Birds (ENBI wp13). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences